Reliability Analysis Using the Monte Carlo Method in the Main Feeders of the Cristianía Substation Belonging to Empresa Eléctrica Quito - Sisa Sisa, Victor Arnulfo (2023)
The presence of failures in the Electric Distribution System (SED) of the primary feeders of Empresa Eléctrica Quito, generated by various causes, cause interruptions in the electric supply to users, where the efficiency of the SED associated with reliability is diminished For this reason, in the present research work, a reliability study is carried out in the primary distribution system of the Cristianía substation through the Monte Carlo Method to optimize the continuity of the electrical service, for which the information of the primary feeders is considered. in the period June 2014 – June 2020 and thus the simulation of the Monte Carlo Method is developed, considering the states of operation, based on the generation of uniformly distributed random numbers for the calculation of forced availability (A) and unavailability (U) and thus obtain the reliability indices at the load point for the period 2021-2023.